Types and functions of indirect communication in prose of I. A. Bunin - Mikhalchuk, Natalya A. (Journal of the Belarusian State University. Philology, 2023)
The problem of indirect communication in I. A. Bunin’s prose of 1900–1930s is studied. The role of indirect utterances in the formation of characters’ speech behaviour is determined. It is proved that in the speech of peasants, evasive answers are common, which are addressed to the landowners and are realised with the help of a number of specifc speech tactics. An important place in the discourses of peasants is occupied by speech acts of allusion, as well as sentence realisations of communicative intentions, among which indirect statements predominate. These types of indirect communication are universal, addressed to various recipients. Allusion speech acts in the discourses of peasants reﬂect their adherence to social norms. It is substantiated that in the speech of landowners, rhetorical questions addressed to representatives of their social class, the main function of the questions is to reduce the categoricalness of statements, are frequent.
Keywords: indirect communication; evasive answer; allusion; sentence realisation of intention